Physiotherapists’ use of airway clearance techniques during an acute exacerbation of bronchiectasis: a survey study - Jennifer Phillips; Annemarie Lee; Rodney Pope; Wayne Hing (Archives of Physiotherapy, 2021)
Abstract Background Airway clearance techniques are recommended for individuals with bronchiectasis both in stable state and during an acute exacerbation, however the current use of airway clearance techniques in the management of individuals during an acute exacerbation is unclear. The aims of this study were to establish what current physiotherapy clinical practice comprises for adults and paediatrics during an acute exacerbation of bronchiectasis; identify physiotherapist’s perceptions of the effectiveness of airway clearance techniques and identify what factors influence their treatment decisions in this population. Methods An anonymous online survey was distributed to the members of the Australian Physiotherapy Association and Physiotherapy New Zealand between August 2016 and April 2017. Results The survey was accessed by 130 physiotherapists and 121 of those deemed themselves eligible and consented to participate. Most participants (89%) reported prescribing airway clearance techniques for 81–100% of individuals during an acute exacerbation of bronchiectasis. The most commonly used airway clearance techniques with adults were huffing (92%), exercise (89%) and the active cycle of breathing technique (89%). The techniques perceived most effective for adults were physical exercise (100%), oscillating positive expiratory pressure devices (97%), directed huffing (95%) the active cycle of breathing technique (90%) and positive expiratory pressure (90%). The most commonly used airway clearance techniques for paediatric patients were: newborn-3 years - percussion (85%) and modified postural drainage (85%); 4–10 years - huffing (100%) and exercise (85%); 11–18 years - huffing (92%) and exercise (77%), active cycle of breathing technique (77%) and positive expiratory pressure therapy (77%). The techniques perceived most effective for paediatric patients were directed huffing (100%), percussion (100%) and positive expiratory pressure via a mask or mouthpiece (93%). The most commonly reported factors influencing choice of technique were patient clinical presentation (72%) and the presence/absence of contra-indications (72%). Conclusion This survey demonstrates that airway clearance techniques are routinely used as part of physiotherapy management of individuals experiencing an acute exacerbation of bronchiectasis, and that choice of technique and perceived effectiveness varies depending on the age of the patient.